Ionic conductivity and phase transitions in solid solutions Na 3 Sc 2(1−x) Yb 2x (PO 4 ) 3 - Салиходжа, Ж. М.; Ногай , А.; Стефанович , С.; Ногай, А. С. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
In this article, the concentration intervals of the existence of single-phase solid solutions Na 3 Sc 2(1−x) Yb 2x (PO 4 ) 3 (x = 0 - 0,03) are established, the regularities concerning the conductive properties and phase transitions of the synthesized samples are studied. The features of ionic conductivity in the α –, β –, γ –phases of the solid solutions under study have been clarified. The behavior of the temperatures of the phase transitions Т α→β and Т β→γ , which occur as a result of the substitution of ytterbium cations for scandium atoms in solid solutions Na 3 Sc 2(1−x) Yb 2x (PO 4 ) 3 , has been established.